HADIS-HADIS PENYAKIT MENULAR (STUDI ‎ANALITIK MATAN HADIS KITAB SHAHIH ‎MUSLIM)‎ - Tamia, Fera; Kamaluddin, Kamaluddin; Siregar, Muhammad Nur (UIN Sumatera Utara Medan, 2020)
The aim of this research is to examine and analyze the texts of hadith in the Sahih Muslim collection regarding infectious diseases, through the hadiths written in this hadith book, Sahih Muslim. The goal is to obtain comprehensive and in-depth data and information about infectious diseases and how to protect oneself from them, as explained both in the book and by medical opinions. In this research, data collection is conducted through library research, utilizing literature relevant to the issue being studied. The hadiths collected in this thesis are obtained using the maudu'i method, which involves gathering hadiths related to the theme of infectious diseases. The collected data is then described using a historical approach and analyzed using content analysis methodology.